Analysis of the Education Value of the Samawa Family at the Reception Before the Marriage Ceremony: Tradition Versus Islamic Sharia Values in the Community Lio Cibarusah Bekasi - Eris Hanifah; Alex Kusmardani; Usep Saepulloh; Hayati Hayati; Said Darnius; Darmawati Darmawati; Fahmi Arfan (UNIVERSITAS SERAMBI MEKKAH, 2022)
This study aims to determine how the law of fiqif in the implementation of walimah urs. And to find out how the implementation of walimah urs before the marriage contract in the Lio Cibarusan Bekasi community. This study uses a qualitative research type located in Kampung Cibrusah Bekasi. The approach used is juridical empirical. The primary sources in this research are husband and wife couples who have done walimah urs as resource persons, while the secondary data are literature research literature on books and journals related to this research. The data collection method is by means of interview observation with analytical descriptive analysis method. The results of the study show that the celebration of the walimatul 'urs wedding party is usually after the marriage contract, its function is to notify that the marriage of a couple has been valid. However, Walimatul Urs before the marriage contract in Kampung Lio Cibarusah Bekasi was against Islamic Family Law as a broken custom.